Ramsar sites in Nepal: Conservation, present scenario, biodiversity value and threats - Shrestha, Binod; Shrestha, Shristi; Shrestha, Arati; Khadka, Udhab Raj (Journal of Wetlands Ecology, 2020)
Wetlands are the dynamic ecosystems with high yielding capacity which are considered very prolific from view point of biodiversity. With prime functioning of water supply, wetlands are well known for supplementary functions of providing ecosystem services viz., groundwater recharge, carbon sequestration, preventing water logging and flooding etc. Total ten wetlands sites of Nepal are included in Ramsar List till 2019, Koshi Tappu being the first listed wetland and Lake Clusters of Pokhara Valley being the latest included wetland which covers 60,561 hectares area of the total area of the country. Ramsar sites in Nepal are distributed throughout the country and are classified as high altitude wetlands, mid hill wetlands and terai wetlands. The Ramsar Site hosts endemic species of floral species some of which are endangered. It too serves as excellent habitat as water hole and corridor for numerous digits of threatened and endangered faunal diversity. Besides this, they serve as excellent habitats for migratory birds as well. Being such integral portions of biosphere, wetlands are under constant threats like eutrophication, siltation, invasion of alien species, pollution, agricultural runoff etc. This review article is based upon desk review different published and unpublished literatures from national level and provides detail information on updated wetlands of international importance of Nepal, along with present scenario, biodiversity value and threats that the wetlands are facing and is expected to help in shaping future course actions for wise use and sustainable management of wetlands in Nepal.